Validation study of computational fluid dynamics models of hemodynamics in the human aorta. Issue 1 (4th September 2019) - Fuchsberger, Jana; Karabelas, Elias; Aigner, Philipp; Schima, Heinrich; Haase, Gundolf; Plank, Gernot
Abstract: We report on conducting a rigorous validation study where we attempt to compare simulated hemodynamics in a mock model of the human aorta with experimental bi‐plane particle image velocimetry (PIV) data. Within the cardiac modeling framework CARP (Cardiac Arrhythmia Research Package) [12] we implemented a finite element CFD solver based on the residual‐based variational multiscale (RBVMS) discretization of the incompressible Navier‐Stokes equations. CFD simulation results compare favorably with experimental PIV data suggesting that our CFD analysis tools are representative of blood flow in the human aorta.